1999
DOI: 10.1046/j.1526-100x.1999.72017.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Reference Data for Assessing and Restoring Headwater Ecosystems

Abstract: Attributes of 25 headwater streams and their associated wetlands were quantitatively sampled in the inner coastal plain of eastern North Carolina. Data from these sites were used to construct and test one functional assessment model (biogeochemical cycling) using the hydrogeomorphic (HGM) approach. Of the 25 sites sampled, 16 unaltered sites were used to establish standards against which field indicators could be compared (indexed). Nine altered sites were used to examine the sensitivity of the model to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 22 publications
(29 reference statements)
1
28
0
Order By: Relevance
“…Process-based restoration is increasingly used in river management (Beechie & Bolton 1999, Rheinhardt et al 1999 and has been suggested to be relevant for Atlantic salmon rivers (Hendry et al 2003, Solomon et al 2003. In particular, the restoration of natural flow regimes has become an important goal in river conservation and restoration, with the expectation that restoring this key process will result in across-the-board improvements in habitat conditions for a wide range or riverine and riparian species (Poff et al 1997).…”
Section: The Process-restoration Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Process-based restoration is increasingly used in river management (Beechie & Bolton 1999, Rheinhardt et al 1999 and has been suggested to be relevant for Atlantic salmon rivers (Hendry et al 2003, Solomon et al 2003. In particular, the restoration of natural flow regimes has become an important goal in river conservation and restoration, with the expectation that restoring this key process will result in across-the-board improvements in habitat conditions for a wide range or riverine and riparian species (Poff et al 1997).…”
Section: The Process-restoration Approachmentioning
confidence: 99%
“…Nislow et al (1999) found that additions of LWD increased the amount of suitable habitat for age-0 salmon in rearing streams of the Connecticut River basin, USA. However, in the absence of appropriate reference systems (Rheinhardt et al 1999), we have little idea how the LWD levels achieved by these habitat manipulations relate to existing loads, or to future loads associated with specific riparian management strategies.…”
Section: Case Study: Riparian Management For Lwd Recruitment In Northmentioning
confidence: 99%
“…To reduce this variability, each constructed marsh was paired with a nearby natural marsh of the same geomorphic position, salinity, and vegetation (S. alterniflora) to serve as a reference against which to measure ecosystem development of individual constructed marshes. Reference wetlands were used to set performance goals for created and restored wetlands (Aronson et al 1993a, b, 1995, Brinson and Rheinhardt 1996, Rheinhardt et al 1999, Whigham 1999). There was some concern, however, that using one or two references site does not capture the dynamic spatial variability among ecosystems of the same type (Pickett and Parker 1994).…”
Section: Site Descriptionmentioning
confidence: 99%
“…IBI are broadly used in state biomonitoring programs to biologically assess environmental from poor water quality and habitat alteration [233][234][235][236]. It compresses categorical metrics for various fish traits (i.e., feeding and reproductive guilds, physiological tolerance) and other ecological indicators (i.e., richness and diversity) into a single score, in which the assessment score is compared with state reference condition scores [237]. The single IBI score is valuable as a screening tool to scope potential restoration projects, but is inadequate for design purposes.…”
Section: Species Functional Traitsmentioning
confidence: 99%
“…By identifying the target species, traits and strategies can be summarized from available databases [113,245]. The suggested target community relies on professional judgement, which is supported by fish surveys from both local reference conditions and ecologically impaired streams, in addition to recolonization potential of different species [211,237,281,282]. After the target fish assemblage (community) has been identified, procedures utilizing species functional traits for restoration design are suggested as follow:…”
Section: Ecohydraulic-based Stream Restoration: Proposed Applicationmentioning
confidence: 99%